Synthesis and Biological evaluation of Oxazolone derivatives - Ashish Dixit; G. Garg; N. P. Sharma; D. K. Shrivastava; A. Sharma (Current Research in Pharmaceutical Sciences, 2011)
Some new [4-[3-chloro-benzylidine]-2-phenyl oxazol-5-one and 4-[2-nitro-benzylidine]-2-phenyl oxazol-4-5-one were synthesized in microwave and there structures were confirmed by I.R. and 1H NMR and their antimicrobial screening against E. Coli, Staphylococcus aureus and Candida albicans were established by zone of inhibition.